Comprehensive Review of Biological Functions and Therapeutic Potential of Perilla Seed Meal Proteins and Peptides - Yangfan Hu; Huan Luo; Vasudeva Reddy Netala; He Li; Zhijun Zhang; Tianyu Hou (Foods)
This comprehensive review explores the biological functions of Perilla frutescens seed proteins and peptides, highlighting their significant potential for health and therapeutic applications. This review delves into the mechanisms through which perilla peptides combat oxidative stress and protect cells from oxidative damage, encompassing free radical scavenging, metal chelating, in vivo antioxidant, and cytoprotective activities. Perilla peptides exhibit robust anti-aging properties by activating the Nrf2 pathway, enhancing cellular antioxidant capacity, and supporting skin health through the promotion of keratinocyte growth, maintenance of collagen integrity, and reduction in senescent cells. Additionally, they demonstrate antidiabetic activity by inhibiting α-amylase and α-glucosidase. The cardioprotective effects of perilla peptides are underscored by ACE-inhibitory activities and combat oxidative stress through enhanced antioxidant defenses. Further, perilla peptides contribute to improved gut health by enhancing beneficial gut flora and reinforcing intestinal barriers. In liver, kidney, and testicular health, they reduce oxidative stress and apoptotic damage while normalizing electrolyte levels and protecting against cyclophosphamide-induced reproductive and endocrine disruptions by restoring hormone synthesis. Promising anticancer potential is also demonstrated by perilla peptides through the inhibition of key cancer cell lines, alongside their anti-inflammatory and immunomodulating activities. Their anti-fatigue effects enhance exercise performance and muscle function, while perilla seed peptide nanoparticles show potential for targeted drug delivery. The diverse applications of perilla peptides support their potential as functional food additives and therapeutic agents.